2014
DOI: 10.1007/s10549-014-3077-5
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelin expression is associated with poor outcomes in breast cancer

Abstract: Background Mesothelin, previously shown to be expressed in triple negative breast cancer (TNBC), is a potential therapeutic target and prognostic marker in breast cancer. Methods We analyzed clinical data from two cohorts comprising of 141 patients treated between 2009 and 2011 at our institution (discovery cohort) and 844 patients from The Cancer Genome Atlas (TCGA) (validation cohort). Mesothelin expression was quantified by immunohistochemistry (IHC) or by RNA transcript levels as measured by whole-transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 19 publications
2
34
0
Order By: Relevance
“…We focused on African-Americans because previous work demonstrated that tumor mesothelin positivity was significantly associated with triple-negative breast cancer (the subtype most common among African-American women) and poor clinical outcomes (35). …”
Section: Resultsmentioning
confidence: 99%
“…We focused on African-Americans because previous work demonstrated that tumor mesothelin positivity was significantly associated with triple-negative breast cancer (the subtype most common among African-American women) and poor clinical outcomes (35). …”
Section: Resultsmentioning
confidence: 99%
“…Because c-Met staining is heterogeneous within and across tumor sections, we used H-score ≥ 30 determined as the product of % positively stained tumor cells and IHC stain intensity (1, 2, or 3 with 3 being the most intense) in three separate high power fields [14, 15], to define (+) c-Met expression.…”
Section: Methodsmentioning
confidence: 99%
“…Prognostication using MSLN immunohistochemistry has been reported in several types of tumors. In breast and lung adenocarcinoma, high-level MSLN expression was reported to be associated with poor prognosis (8,9,12). In contrast, prolonged survival in patients with MSLN-expressing tumors was noted in ovarian serous and thymic carcinomas as well as malignant pleural mesothelioma (11,13,14).…”
Section: Introductionmentioning
confidence: 99%